2019
DOI: 10.4049/jimmunol.1801069
|View full text |Cite
|
Sign up to set email alerts
|

The Immune Function of Tuft Cells at Gut Mucosal Surfaces and Beyond

Abstract: Tuft cells were first discovered in epithelial barriers decades ago, but their function remained unclear until recently. In the last 2 years, a series of studies has provided important advances that link tuft cells to infectious diseases and the host immune responses. Broadly, a model has emerged in which tuft cells use chemosensing to monitor their surroundings and translate environmental signals into effector functions that regulate immune responses in the underlying tissue. In this article, we review the cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
79
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 88 publications
(83 citation statements)
references
References 105 publications
(209 reference statements)
1
79
0
Order By: Relevance
“…In the gut, it has been shown that tuft cell-derived IL-25 is required to mount a Th2 immune response to parasite infection. Tuft cell-derived IL-25 stimulates group 2 innate lymphoid cells (ILC2s) to produce IL-5, -9, and -13, promoting type 2 inflammation (Ting and von Moltke, 2019). IL-13 is sufficient to skew the lineage of undifferentiated intestinal epithelial cells toward tuft and mucin-producing goblet cells.…”
Section: Discussionmentioning
confidence: 99%
“…In the gut, it has been shown that tuft cell-derived IL-25 is required to mount a Th2 immune response to parasite infection. Tuft cell-derived IL-25 stimulates group 2 innate lymphoid cells (ILC2s) to produce IL-5, -9, and -13, promoting type 2 inflammation (Ting and von Moltke, 2019). IL-13 is sufficient to skew the lineage of undifferentiated intestinal epithelial cells toward tuft and mucin-producing goblet cells.…”
Section: Discussionmentioning
confidence: 99%
“…6a). We next utilized gene set enrichment analysis (GSEA) to compare the transcriptome of drug treated BPN tumors to published/curated gene expression datasets for gastric epithelial cell types and tuft cells (Haber et al 2017;Leushacke et al 2017;Montoro et al 2018;Ting and von Moltke 2019;Zhang et al 2019). GSEA showed that signatures of both Lgr5-expressing gastric chief cells as well as tuft cells were significantly enriched in MAPK-inhibited BPN cells ( Fig.…”
Section: Mapk Pathway Regulates Identity Of Nkx2-1-negative Mucinousmentioning
confidence: 99%
“…Likewise, goblet cells secrete mucins and antimicrobials that are effective against bacteria and protozoa (Kim and Ho, 2010). On the other hand, tuft cells express IL-25 that is important in mounting a type 2 immune response to protect against certain helminths (Ting and von Moltke, 2019). Finally, different pathogens elicit different immune responses that result in an alteration of the intestinal epithelial cell composition that is important for effector responses (Biton et al, 2018;Lindholm et al, 2020).…”
Section: Introductionmentioning
confidence: 99%